Personal cost of reporting and status of wrongdoer: experimental study pf whistleblowing intention / Claudia Vinska Vinancia, Intiyas Utami and Nafsiah Mohamed. - Vinancia, Claudia Vinska; Utami, Intiyas; Mohamed, Nafsiah (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2019)
Whistleblowing is an important action for the organization as a form of internal control of illegal actions that cause losses. This study aimed to test of causality of the personal cost of reporting and status of the wrongdoer on whistleblowing intention. This study used a true experimental design between subjects 2x2. The subjects of this study were 95 accounting study program students. The students acted as the government’s internal auditor. The results of this study indicate that whistleblowing intentions will be higher in personal cost of reporting and the status of the wrongdoer low compared to personal cost of reporting and status of wrongdoer high. A whistleblower prefers not to perform whistleblowing when the wrongdoer has a higher position and sanctions to be received are severe.